2009
DOI: 10.1002/qua.22072
|View full text |Cite
|
Sign up to set email alerts
|

Electronic effects and ring strain influences on the electron uptake by selenium‐containing bonds

Abstract: International audienceThe gas-phase electron attachment of thiaselena and diselena derivatives is investigated on model organic systems by ab initio calculations (level of theory MP2/DZP++). Electronic contributions favor the one-electron addition on selenium-containing compounds, with adiabatic electron affinities of 0.03, 0.24, and 0.43 eV, respectively, for dimethyldisulfide, dimethylselenenylsulfide, and dimethyldiselenide. This ensures the possibility of an excess electron binding on [BOND]Se[BOND]S[BOND]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 47 publications
0
15
0
Order By: Relevance
“…3(a)]: evolution is directed towards lenghtening only, which is justified by the universal dissymmetry of Morse curves. The latter can be found in Figure 4 in Reference [33]. In contrast, corresponding RA hemi-bonds exhibit much larger deviations, by up to 0.15 Å [n = 0 for dithia and selenylsulfide linkages, Fig.…”
Section: Structurementioning
confidence: 86%
See 2 more Smart Citations
“…3(a)]: evolution is directed towards lenghtening only, which is justified by the universal dissymmetry of Morse curves. The latter can be found in Figure 4 in Reference [33]. In contrast, corresponding RA hemi-bonds exhibit much larger deviations, by up to 0.15 Å [n = 0 for dithia and selenylsulfide linkages, Fig.…”
Section: Structurementioning
confidence: 86%
“…The latter was generalized to selenylsulfide -S-Se-and diselenide -Se-Se-linkages [33]. Explicit treatment of electron correlation is mandatory for a correct evaluation of geometries and adiabatic electron affinities (AEAs) [34].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, Dumont et al [1] used ab initio calculations to investigate the gas-phase electron addition on selenium-containing organic compounds, dimethyldisulfide, dimethylseleneylsulfide, and dimethyldiselenide. It is found that selenium strongly enhances the electron Figure 2.…”
Section: Cleavages Of S-s S-se and S-se Bondsmentioning
confidence: 99%
“…Previous studies have been mainly focused on using theoretical calculations to study the effects of electron capture on small diselenide compounds (XSeSeX'), such as CH 3 SeSeCH 3 , CH3SeSeOH, CH3SeSeF, and such [1,[32][33][34][35]. So, it is of interest to examine the ECD behavior of diselenide peptides compared with previous theoretical calculations, and also to examine the differences and similarities of the ECD fragmentation patterns among disulfide (S-S), sulfur-selenium (S-Se), and diselenide (Se-Se) peptides.…”
Section: Introductionmentioning
confidence: 99%